2.8 W, 90 nJ, 114 fs Yb: YAG thin-disk pumped degenerate optical parametric oscillator at 2.06 µm - Li, Anni; Bahri, Mehran; Gray, Robert M.; Choi, Seowon; Hoseinkhaniasl, Sajjad; Srivastava, Anchit; Marandi, Alireza; Fattahi, Hanieh (High Intensity Lasers and High Field Phenomena, HILAS 2024 in Proceedings High-Brightness Sources and Light-Driven Interactions Congress - Part of Optica High-Brightness Sources and Light-Driven Interactions Congress, 2024)
We present unprecedented 2.8 W, 90 nJ, 114 fs, 30.9 MHz pulses at 2.06 µm from a degenerate optical parametric oscillator pumped by a high-power Yb:YAG thin-disk oscillator.
CRIS-Team Scopus Importer:2024-10-04